The Influence of Al-Mauizah Al-Hasanah Preaching Method on the Problems of Students in Alurwatul Wutsqaa Islamic Boarding School in Sidenreng Rappang Regency. - Syahrul, Isriwanda; Tajibu, Kamaluddin; Muhammad, Firdaus (Jurnal Mercusuar, 2021)
This research is located at the Al-Urwatul Wutsqaa Islamic Boarding School in Sidenreng Rappang Regency, with the title "The Influence of Al-Mauizah Al-Hasanah Da'wah Method on the Problems of Students at Al-Urwatul Wutsqaa Islamic Boarding School in Sidenreng Regency". Based on this theme, three research objectives were formulated, namely: first, to describe the Al-Muaizah Al-Hasanah da'wah method; second, to describe the problems of students; third, whether there is an influence of the Al-Mauizah Al-Hasanah da'wah method on the problems of students at Al-Urwatul Wutsqaa Islamic Boarding School in Sidenreng Regency.This research is a survey research using a quantitative approach. The data obtained was processed descriptively and quantitatively. Based on the regression analysis conducted on the research data, the results are as follows: (1) the Al-Mauizah Al-Hasanah Da'wah Method at Al-Urwatul Wutsqaa Islamic Boarding School shows accurate results with a percentage of 60%, (2) the problems of students at Al-Urwatul Wutsqaa Islamic Boarding School show a decrease with a percentage of 48.9%, (3) there is a positive and significant influence as indicated by the t-value>t table (4.734>0.00116). The influence is 53%, with the effective contributions of each component of the Al-Mauizah Al-Hasanah da'wah method on the problems of students being love and compassion by 25%, gentleness by 24%, and psychological touch by 24%.